Analisis Kemampuan Mahasiswa Calon Guru SD dalam Merancang Model Pembelajaran Inkuiri pada Mata Pelajaran IPA Sekolah Dasar: Analysis of the Ability of Prospective Elementary Teacher Candidates in Designing Inquiry Learning Models in Elementary Science Subjects - Rusdiyana, Rusdiyana (Anterior Jurnal, 2025)
Learning plans are essential in providing an effective learning environment. This research aims to analyze the ability of prospective elementary school teacher candidates in designing inquiry learning models through lectures on science material and learning in elementary schools. This type of research is quantitative with descriptive analysis. The research was carried out in the even semester of the 2022/2023 academic year at Achmad Yani University, Banjarmasin, South Kalimantan. Data collection was carried out using a quantitative approach through performance assessments. The research population was 87 PGSD students, and the sample consisted of 24 PGSD Semester 6 students who took science material and learning lectures at elementary school.  The data were analyzed descriptively to describe the average ability of students to prepare learning plans, teacher books, and student books. The results of the research show that the competencies of PGSD students at Achmad Yani University Banjarmasin in designing inquiry learning models include the ability to: design learning plans, compile teacher books and student books that meet the criteria for effective achievement. Only the indicators of the use of ICT-based learning media and attractively designed teaching materials resulted in ineffective assessment results.